Ilqam Learning & Leading Programmes 2010/ Institut Kepimpinan dan Pengurusan Kualiti (iLQAM), UiTM - UiTM, iLQAM (Institut Kepimpinan dan Pengurusan Kualiti (iLQAM), UiTM, 2010)
The Institute of Leadership and Quality Management, also known as iLQAM, was established on 1 March 2003 in line with the requirements of IPTA Quality Assurance 2002 of the Ministry of Education of Malaysia and the restructuring of UiTM 2001-2010. iLQAM was set up with the objective of fulfilling the University responsibility of providing a wide spectrum of training and professional development programmes for its academics staff. This programmes are designed specifically to meet the varying needs of the academic staff, from basic teaching and learning courses to leadership courses. A qualified and highly developed cadre of academics would indeed enhance and strengthen the teaching, learning and researching dimensions of the university. iLQAM is guided by the vision and mission of UiTM in the planning, implementing and monitoring of all its programmes.